Modification Of Base Genep Instant Bali Seasoning Using Fdh6 Type Dehydrator - Pramudia, Heru; Tanius, Billy (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
This research concerns the findings of the formulation of the balinese seasoning base genep dry instant, related to the formulation of spices for balinese specialties which so far are in pasta packaging or are generally known as the seasoning wet base genep. Through food technology applications, this spice is dried using a dehydrator machine. This dry seasoning is expected to be easier and more efficient to use in various balinese dishes, and durable in storage. The methodology of this research is experimental, with steps to standardize the appropriate seasoning recipe, dry the seasoning with a dehydrator, and apply the dry seasoning for using in chicken betutu. Then do a preference level assessment test by expert panelists. The expert panelists used in this study were members of the Indonesian Chef Association Bali (ICA Bali). All panelists work as cooks or chefs and are native balinese who are accustomed to enjoying betutu chicken for generations. The results of the research on the level of preference for this instant seasoning are on average at a score of 4. This means that the panelists like the taste, aroma, texture, and color of using base genep seasoning. As we know in using of instant seasoning, being increasingly popular in the catering, hotel, and restaurant industries. This provides an opportunity to produce base genep instant seasoning on an industrial scale.